The Influence of Family Education and Green School Culture on Student’s Green Consumer: Behavior the Mediating Role of Peer Group Support - Susanti Kurniawati; Ardika Sulaeman; Hamdan Ardiansyah (Economics Education Department Universitas Negeri Semarang, 2024)
The background of this research was environmental degradation which affects life quality now and in the future. This study aims to assess the influence of family education and green school culture on green consumer behavior among high school students. This research method was a survey research design, with a population of high school students. Using simple random sampling, 235 students were selected. Data were collected through questionnaires and interviews and analyzed using descriptive and inferential statistics with PLS- SEM. Results stated that Family education and green school culture were found to influence green consumer behavior. While peer group support did not mediate the effect of family education, it did mediate the influence of green school culture on green consumer behavior. The study highlights the importance of family and school environments in shaping environmentally conscious behaviors, with peer group support as a significant mediator in school-based influences. The implication of this research was in order to promote green consumer behavior, it is crucial to incorporate environmental education into the curriculum, according to research on green consumer behavior. Educational programs can successfully encourage pro-environmental actions by emphasizing the improvement of attitudes, knowledge, and social norms.